KONSEP KEPENTINGAN UMUM DALAM PENGADAAN TANAH DIHUBUNGKAN DENGAN KEPASTIAN HUKUM (Jurnal Hukum Mimbar Justitia, 2020)
The debate arises regarding the meaning of the concept of public interest. The concept of public interest changes, not the same/different so it is not clear, not firm and not standard, both in regulations, in the opinion of experts, in court decisions, and the implementation of land acquisition. As a result of the concept of public interest is interpreted differently, namely interpreted in the interests of the private, business (commercial) and financiers to seek maximum profits. The research approach used is juridical normative, with the nature of descriptive-analytical research. The research source uses secondary data consisting of primary, secondary, and tertiary legal materials. The results of the first research are the concept of public interest in land acquisition, that the concept of public interest is regulated in several laws and regulations, in the opinion of experts, court decisions, and implementation of non-standard land acquisition. The concept of public interest in Article 1 Number (6) of Law No. 2 of 2012 is not clear. For this reason, the concept of public interest is made standard so that it is not interpreted differently, that is, interpreted for business purposes in the context of seeking profit. If interpreted for business purposes, it is not useful for everyone, including the community and the state. The results of the research of the two concepts of public interest in the land acquisition are related to legal certainty, that the concept of public interest is regulated in several laws and regulations, in the opinion of experts, court decisions, and the implementation of non-standard land acquisition, then there is no legal certainty. The concept of public interest in Article 1 Number (6) of Law No. 2 of 2012 is unclear which ultimately does not provide legal certainty. The meaning of legal certainty is order, what is allowed, and what is not allowed. To guarantee legal certainty, the concept of public interest in the article is added to the element of public interest that is not for business purposes, so that the article is in the interest of the nation, state, and society as much as possible for the prosperity of the people and not for business. Keywords : Public Interest, Land Acquisition, Benefit Principle.